Human urogenital myiasis: A systematic review of reported cases from 1975 to 2017. (April 2019) - Faridnia, Roghiyeh; Soosaraei, Masoud; Kalani, Hamed; Fakhar, Mahdi; Jokelainen, Pikka; Zolfaghari Emameh, Reza; Banimostafavi, Elham Sadat; Ziaei Hezarjaribi, Hajar
Abstract: The public health importance of myiasis [infestation with dipterous (fly) larvae] remains unknown. This disease is spread worldwide in animals and humans, but baseline data on its prevalence are limited. In particular, knowledge on human urogenital myiasis (UGM) is scattered. As such, a systematic search was undertaken of five English and five Persian databases for publications describing UGM cases in English or Persian published between 1975 and 2017. In total, 45 papers reporting 59 UGM cases from various regions of the world are included in this review. All included papers were from the English databases. The age of patients ranged from 5 to 89 years, and the mean age was 40.6 years. Thirty-six of the patients were female and 19 were male. The highest number of cases ( n = 12) was reported from Brazil. The most common genera causing UGM were Psychoda spp. (23.7%) and Cochliomyia spp. (11.8%). The vagina was the most commonly reported anatomical location of UGM for women, and the urogenital tract was the most commonly reported location for men. Thirteen cases were reported from rural areas and eight cases from urban areas; the location of other cases was not specified. The incidence of UGM is likely to be substantially underestimated when evaluated based on published case reports. Epidemiological studies, such as questionnaires to medical doctors, could help to gather the necessary baseline data on the occurrence of UGM.